COVID-19 Recovery Patterns Across Alpha (B.1.1.7) and Delta (B.1.617.2) Variants of SARS-CoV-2 - Kumar, Nitya; Quadri, Suha; AlAwadhi, Abdulla Ismaeel; AlQahtani, Manaf (Frontiers in Immunology, 2022)
Background: B.1.1.7 (alpha) and B.1.617.2 (delta) variants of concern for SARS-CoV-2 have been reported to have differential infectivity and pathogenicity. Difference in recovery patterns across these variants and the interaction with vaccination status has not been reported in population-based studies. Objective: To study the length of stay and temporal trends in RT-PCR cycle times (Ct) across alpha and delta variants of SARS-CoV-2 between vaccinated and unvaccinated individuals. Methods: Participants consisted of patients admitted to national COVID-19 treatment facilities if they had a positive RT-PCR test for SARS-CoV-2 and analysis of variants was performed (using whole genome sequencing). Information on vaccination status, age, sex, cycle times (Ct) for four consecutive RT-PCR tests conducted during hospital stay and total length of hospital stay for each participant were ascertained from electronic medical records. Results: Patients infected with the delta variant were younger (mean age = 35years vs 39 years for alpha, p<0.001) and had lesser vaccination coverage (54% vs 72% for alpha, p<0.001). RT-PCR Ct values were similar for both variants at the baseline test, however by the fourth test, delta variant patients had significantly lower Ct values (27 vs 29, p=0.05). Length of hospital stay was significantly higher in delta variant patients in vaccinated (3 days vs 2.9 days for alpha variant) as well as in unvaccinated patients (5.2 days vs 4.4 days for alpha variant, p<0.001). Hazards of hospital discharge after adjusting for vaccination status, age and sex was higher for alpha variant infections (HR=1.2, 95% CI: 1.01 – 1.41, p=0.029). Conclusion: Patients infected with delta variant of SARS-CoV-2 were found to have a slower recovery as indicated by longer length of stay and higher shedding of the virus compared to alpha variant infections and this trend was consistent in both vaccinated and unvaccinated patients.